PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN TERBALIK (RECIPROPCAL TEACHING) DENGAN PEMANFAATAN INTERNET PADA KONSEP LAJU REAKSI KELAS XI A-1 SMA NEGERI 1 BANJARMASIN TAHUN PELAJARAN 2009/2010 - Erlidayanti Erlidayanti; Rilia Iriani; Leny Leny (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2010)
Abstract: The classroom action research implementing reciprocal instructional model by using internet as a learning source on kinetics reaction concept was conducted. The research purposes are to increase learning outcome, affective ability and student respond to the implementation of reciprocal model. The subject research involved class XI of SMAN 1 Banjarmasin. It was found that student’s comprehention increased from 73,85% at first cycle to 94,62% at second cycle, student’s affective ability in a good category and student’s gave a positive respon to the implementation of reciprocal instructional model at teaching and learning process.Key word : Reciprocal teaching, kinetics reaction, internet